Ksztaltowanie koordynacyjnych zdolnosci motorycznych (KZM) w systemie wieloletniego przygotowania sportowców - Lyakh, V.; Sadowski, J.; Witkowski, Z. (Polish Journal of Sport and Tourism, 2011)
The article attempts to summarize the current knowledge on the preparation of coordination in combat sports and team games. It has been discussed: the basic principles of CMA training, complexity of coordination exercises, the duration of load and rest breaks, the systematic use of special exercises creating the most important CMA and factor of sensitivity and lateralisation in the development of CMA. The directions for further researches have been marked out.